Determinantes de la demanda de depósitos en moneda nacional del sistema financiero de Loreto periodo 2017 – 2021 - Cruz Pizango, Dirk Anderson (2023)
The present research work aims to analyze and verify which are the determining factors of the demand for deposits in national currency of the financial system of Loreto. For this purpose, the average passive interest rate in national currency of the Peruvian financial system, the nominal exchange rate, and the inflation rate of Loreto are proposed as candidate variables. Within this thesis, appropriate econometric methods and tests were used to obtain reliable and concise results, taking into account the hypotheses raised in the research. According to the resulting estimates, it was evidenced that only the interest rate and the exchange rate are determining factors of the demand for deposits; however, considering the results of the multicollinearity test, it is verified that only the nominal exchange rate is a relevant determining factor.